2012
DOI: 10.5296/jbls.v3i1.2218
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Phytochemical Compositions of the Leaves of Mucuna Poggei

Abstract: The chemical nutrient composition and the phytochemical content of the leaves of Mucuna poggei, an underutilized leafy vegetable were analyzed using standard methods. The result of the proximate compositions analysis showed that the leaves contained moisture (8.25%), crude fibre (30.55%), crude fat (9.45%), ash (7.78%), crude protein (32.38%) and carbohydrate (11.55%). Results of the mineral analysis showed that it contains the following essential minerals: Sodium (68.10mg/100g), potassium (43.21mg/100g), calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…Gordon and Kessel (2002) reported that low fat foods help to reduce cholesterol level and obesity. The total carbohydrate content found in this study was comparable to the value obtained from F. capensis bark but much higher than the value for F. capensis leaves (Uzokwe et al, 2013) but the total carbohydrate content indicated by Oko et al, (2012) for U. trimervis was much lower.…”
Section: Discussionsupporting
confidence: 69%
“…Gordon and Kessel (2002) reported that low fat foods help to reduce cholesterol level and obesity. The total carbohydrate content found in this study was comparable to the value obtained from F. capensis bark but much higher than the value for F. capensis leaves (Uzokwe et al, 2013) but the total carbohydrate content indicated by Oko et al, (2012) for U. trimervis was much lower.…”
Section: Discussionsupporting
confidence: 69%
“…The crude protein content obtained in the study (16.08% ± 0.17%) was high compared with the 1.98% reported for Securinega virosa leaves (Danlami, David & Thomas 2012), but considerably lower than some other vegetables like Ocimum gratissimum, Gnetum africanum and Vernonia amygdalina (Dike 2010). The value obtained for carbohydrate in C. cujete (40.48% ± 0.11%) was higher than the values obtained for Urera trimervis (6.07%) and Mucuna poggei (11.55%) (Oko et al 2012;Sofowora 1993), but was lower when compared with the 54.71%, 55.75%, 59.70%, 53.30% and 54.72% obtained for Morinda lucida, Landolphia hirsuta, Elaeis guineensis, Pterocarpus soyauxii and Vernonia amygdalina, respectively (Dike 2000). The results obtained indicate that the leaves of C. cujete are a good source of fibre, minerals (ash), protein and energy, but not a good source of edible fat.…”
Section: Proximate Analysiscontrasting
confidence: 69%
“…Phosphorus content was found to be 1.50 mg/100 g ± 0.001 mg/100 g. Phosphorus plays an important role in normal kidney functioning, transfer of nerve impulse and ionic balance in the blood and tissues as reported by Ahmed and Chandhary (2009). Magnesium content of the leaves was found to be 2.07 m/100 g ± 0.012 mg/100 g, which was relatively lower than 56.05 mg/100 g ± 0.012 mg/100 g reported by Oko et al (2012) for Mucuna poggei leaves and 2.56 mg/100 g for Diospyros mespiliformis (Hassan et al 2004). Magnesium is an activator of coenzymes in carbohydrates and protein metabolism as claimed by Vormann (2003).…”
Section: Mineral Analysismentioning
confidence: 70%
“…The result of Iron content of M. arboreus was 7.44mg/100g which was lower than the value found in Ocimum viridis and Ocimum gratissimum (34). Iron content of S. sporgonophora was 10.58g/100mg which is high when compared with the value obtained for Tribulus terrestris "Tsada" and in some cultivated vegetables such as spinach, lettuce and cabbage but compared favourably with values found in Mucuna poggei (10.58mg/100g) (20) and Ocimum gratissimum (10.32mg/100g) (34). Green vegetables are recommended for anemic convalescence.…”
Section: Phytochemical Screeningmentioning
confidence: 59%
“…The moderate amount of fat in the leaves shows that the vegetables are not source of lipid accumulation. Crude lipids, though serves as principal sources of energy should be consumed with caution so as to avoid obesity and other related diseases (20). The carbohydrate content of the leaves was within the range of (1.22%-15.90%) reported for some selected Nigerian leafy vegetables (21).…”
Section: Phytochemical Screeningmentioning
confidence: 79%